IL‐12 and IFN‐γ in Response to Leishmania Infantum Antigens in Felines From an Endemic Area for Visceral Leishmaniasis - Lode, João Victor Lé [UNESP]; Ito, Lucas Takeshi Siqueira [UNESP]; Umino, Gisele Mitsue [UNESP]; de Lima, Valéria Marçal Felix [UNESP] (Wiley, 2025)
Visceral leishmaniasis is a potentially fatal zoonosis with an increasing incidence. Most infected felines present the disease in its subclinical form and demonstrate greater resistance to parasitemia than dogs. However, the role of cellular immunity in felines is still poorly understood. This study measured serum levels of interleukin (IL)-12 and interferon-gamma (IFN-γ) in asymptomatic cats naturally infected with antibodies against Leishmania spp. and in uninfected cats. IL-12 and IFN-γ were measured in serum samples by ELISA. Parasite load quantification was performed on DNA from bone marrow samples using qPCR. Cats naturally infected by Leishmania spp. showed significantly higher serum levels of IL-12 and IFN-γ compared to control animals. IL-12 showed a positive correlation with IFN-γ suggesting a regulatory role of IL-12 in activating the Th1 immune response, which enhances macrophage function and promotes intracellular parasite elimination. Additionally, IL-12 showed a moderate negative correlation with parasite load, indicating a protective effect of IL-12 in feline leishmaniasis. These findings suggest that IL-12 and IFN-γ play critical roles in modulating the feline immune response against parasitic infection, possibly contributing to the control of parasite replication and in the prevention of clinical signs. The immune response observed in felines could be explored for future immunotherapeutic approaches, helping to mitigate the progression of leishmaniasis in cats and reducing the risk of transmission in endemic regions.